The South Kalimantan Provincial Election Commission's Strategy to Increase First-Time Voters in the 2024 South Kalimantan Gubernatorial Election - Ramadani, Mustafa (West Science Law and Human Rights, 2025)
This study examines the strategy of the General Elections Commission (KPU) of South Kalimantan Province in increasing the participation of first-time voters in the 2024 South Kalimantan Gubernatorial Election (Pilgub). The study used a descriptive qualitative approach with data collection techniques through in-depth interviews with KPU South Kalimantan commissioners and data obtained from official KPU South Kalimantan reports. The results show that the KPU South Kalimantan implemented a multidimensional political communication strategy through educational, participatory, and digital approaches. Several main programs carried out included the Election Procession activities, the launch of the "Bekantan" mascot, outreach at universities, and collaboration with mass media and youth organizations. The use of social media such as Instagram, YouTube, and X (Twitter) was also carried out interactively through quizzes with prizes to attract the attention of first-time voters. This effort proved effective with an increase in the number of first-time voters from 277,777 in the 2020 Pilgub to 702,500 in the 2024 Pilgub. However, the KPU South Kalimantan still faces obstacles, such as limited budget for outreach and the lack of grouping of voter data by age category. This research emphasizes the importance of sustainable, data-driven, and inclusive political communication strategies to strengthen youth participation in local democracy.